On-farm surveys and field experiments identify genotype and management practices to increase dryland winter wheat grain yield - Jaenisch, Brent Robert (Kansas State University, 2021)
Wheat yields are variable in dryland environments due to the erratic weather regime and the consequent conservative management practices adopted by producers, leading to large yield gaps. Our objectives were to disentangle management x genotype interactions and identify management practices associated with increased wheat yield in dryland Kansas environments. Producer-reported yield and management data were collected from 656 commercial fields during the 2016-18 harvest seasons, including 43 management practices, five weather, and two soil variables. Grain yield ranged from 0.3 to 7.1 Mg ha⁻¹ with yield gap averaging 44%. Foliar fungicide, nitrogen (N) rate, and method were the most common management strategies to affect yield. Two field experiments were conducted during 2018, 2019, and 2020 in several Kansas environments. In experiment one, we evaluated the grain yield response of four commercial wheat varieties to six different management intensities in six environments. Across environments and genotypes, managing for the yield potential increased yield by 1.4 Mg ha⁻¹ (30%) as compared to the farmer practice. Aboveground biomass and kernel number related more strongly to yield than harvest index and kernel weight. Experiment two evaluated the colimitation of nitrogen (N) and sulfur (S) to wheat yield and its effects on N and S use efficiencies (and its components of uptake and utilization) in eight environments. Across environments, wheat grain yield increased with increases in N rate; however, S application only increased grain yield at two environments. Minimum N and S uptake to maximize yield at 5.7 Mg ha⁻¹ was 120 and 7 kg ha⁻¹. Nitrogen limitation impacted S use efficiency and vice versa, and the limitation of both nutrients increased the wheat yield gap. This research identified several genotype x management practices associated with wheat yield in commercial and experimental settings, and reinforced the need for integrated management practices according to site-specific limitations to improve wheat yields.
Keywords: Winter wheat; On-farm survey; Yield Components; NxS colimitation